Evaluation of wheat (Triticum aestivum) germplasm and varieties against stem rust (Puccinia graminis f. sp. tritici) pathotype Ug99 and its variants - S.C. BHARDWAJ, M. PRASHAR, R. CHATRATH, V. TIWARI, MANGAL SINGH; INDU SHARMA, A.K. SHARMA*, M.S. SAHARAN (Indian Phytopathology, 2015)
The studies were undertaken to identify resistance to Ug99 in wheat (Triticum aestivum L.) germplasm and popular varieties in East Africa (Kenya and Ethiopia) during 2005-2011. During 2005, out of 22 lines, three genetic stocks, FLW 2 (PBW 343 + Sr24), FLW 6 (HP 1633 + Sr24) and FLW 8 (HI 1077 + Sr25) were found resistant along with HW 1085. Subsequently, 102, 318, 420, 241 and 189 lines consisting of elite advanced lines, along with released varieties were evaluated during 2006, 2008, 2009, 2010 and 2011, respectively, in Kenya and Ethiopia against stem rust (Puccinia graminis f. sp. tritici) pathotype Ug99 and its variants. Wheat lines, viz. A-9-30-1, AKDW 4021, DDK 1037, DDK 1038, DDW 14, DL 153-2, GW 1250, HD 2781, HD 3014, HD 4720, HDR 77, HI 8381, HI 8498, HUW 234, HW 5211, K 9107, MACS 1967, MACS 2846, MACS 2988, MACS 2998, MACS 3742, MACS 5009, MPO 1215, NI 5439, NIDW 295, PBW 315, PBW 612, PDW 274, PDW 316, PDW 317, WH 147, Sr22, Sr32, Sr35, Sr39, Sr42 and triticale varieties TL 2942, TL 2963 and TL 2966, showed resistance to Ug99 and its variants (Ug99TTKS and TTKSK) on evaluation in Kenya and Ethiopia during 2006-2011. During 2010, slow ruster lines for Ug99 resistance were identified based on AUDPC values. These lines may be utilized for improving Ug99 resistance in popular Indian wheat cultivars.